Beyond one-size-fits-all in cardiogenic shock: impella, extracorporeal membrane oxygenation or tailored use of mechanical circulatory support - Rob, Daniel; Belohlavek, Jan (Current opinion in critical care, 2024)
PURPOSE OF REVIEW: This article offers an overview of recent randomized controlled trials (RCTs) testing the efficacy of veno-arterial extracorporeal membrane oxygenation (VA ECMO) and microaxial flow pump (mAFP) in treating cardiogenic shock, including findings from the DanGer shock trial. It summarizes the clinical implications and limitations of these studies and key decision-making considerations for cardiogenic shock device use. RECENT FINDINGS: Despite important limitations in all published RCTs, the routine use of VA ECMO for acute myocardial infarction related cardiogenic shock did not demonstrate benefit and should be reserved for selected patients with extreme forms of cardiogenic shock. Conversely, mAFP (Impella CP) appears promising for cardiogenic shock due to ST elevation myocardial infarction. A stepwise approach - initial mAFP use for cardiogenic shock with left ventricular failure, supplemented by VA ECMO if mAFP is inadequate or if severe right ventricular failure is present - may be preferable, but requires validation through RCTs. High complication rates in device arms underscore the need for careful patient selection, preventive strategies, education for centers and operators, and further research. SUMMARY: Recent trials offer insights into mechanical circulatory support in cardiogenic shock, but their real-world applicability is limited. Despite potential benefits, the use of VA ECMO and mAFP is associated with significant complication rates, emphasizing the need for personalized use.
Keywords: výsledek terapie; Extracorporeal Membrane Oxygenation; Patient Selection; podpůrné srdeční systémy; Treatment Outcome; randomizované kontrolované studie jako téma; Heart-Assist Devices; mimotělní membránová oxygenace; lidé; výběr pacientů; Humans; kardiogenní šok; Randomized Controlled Trials as Topic; Shock, Cardiogenic